HUBUNGAN PENGETAHUAN SUAMI TENTANG HAK REPRODUKSI PEREMPUAN DENGAN PERAN SUAMI DALAM PENCEGAHAN KEMATIAN IBU DI DESA KARANGGAMBAS KECAMATAN PADAMARA KABUPATEN PURBALINGGA - Ilmawati, Siti; Wardhianna, Sotyania; Sistiarani, Colti (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2011)
ABSTRACT One of the reasons of persistent high maternal mortality rate (MMR) in Indonesia,is lack of husband?s involvement in caring for a pregnant wife and childbirth and lack of participation in family planning program, husband considers women's reproductive health, while decision-makers in the family is held by husband and decision making in reproductive health. One of the factors causing low role of the husband is the low knowledge of reproductive rights. Purpose of the study is to determine the relationship of knowledge about reproductive rights of women with role of the husband in the prevention of maternal mortality in people Karanggambas Padamara Purbalingga district. This research is explanatory research and survey research method with cross sectional studies. The population of the study are all husbands who have young children aged 0-12 months living in the village of Karanggambas Padamara area the number was 89 husbands. Husband with a total of 49 samples using cluster random sampling technique. Data analysis Univariate and bivariate analysis (Spearman Rank) and test Correlation Coefficient (CC). The results showed knowledge of the reproductive rights of women in the high category (63.3%). The role of husbands in the prevention of maternal deaths in the category of play (59.2%). There is a correlation between husband's knowledge about reproductive rights of women with her husband's role in the prevention of maternal mortality in people Karanggambas Padamara Purbalingga district (p = 0.001). Recommended for the husband who still has a low knowledge, should increase knowledge about reproductive rights and role in the prevention of maternal mortality through health education actively followed. Keywords : knowledge, husband, maternal mortality Kesmasindo. Volume 4,(1)Januari 2011, hlm. 38-46